TRAUMA INFORMED AND SENSITIVE SCHOOLS (Heritage, 2021)
Adverse childhood experiences and traumatization puts impact on children's ability to learn and have potential effects on education process. Traumatization, which occurs at the earliest age, can cause a negative impact on the brain and child cognitive development. In school-age children, problems with concentration and reduced ability to sit still and attend classes can in the long run lead to problems in achieving school success, behavior, self-regulation, as well as difficulties in establishing and maintaining relationships with peers and adults. In trauma informed schools, teachers and school staff know the living conditions of children in the school, they are able to recognize and address needs of traumatized children and understand the trauma effects on children and adults wellbeing. Teachers and school staff are able to identify students who are in need of help, due to trauma and they are able to respond to their needs. Potential impact of continual exposure to child narratives and experiences of trauma inevitably affects teachers and requires training on how to protect themselves from vicarious trauma. Implementing and developing trauma informed schools would indirectly influence the increase of educational achievement in children and youth with experience of traumatization. School success contibutes to strenghtening traumatized children’s resiliance.
Keywords: academic achievement, adverse childhood experiences, trauma, trauma informed practice, trauma-informed schools